Analysis of the Sales Process of Red Onion Seeds of Nganjuk Variety through Educational YouTube Content Marketing - Yuliansyah, Dandy; Askafi, Eka; Mulyaningtyas, Ratna (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research is motivated by the rapid development of information technology, especially digital media such as YouTube, which brings significant transformation to companies' marketing paradigms, particularly in the agricultural sector. This study aims to describe the educational-based content marketing process implemented on the Gusman Bojonegoro YouTube channel and its impact on the sales of Nganjuk shallot seeds. This research uses a qualitative method with a descriptive approach. Data were collected through interviews, direct observation, and documentation from various informants, including the channel owner, nursery warehouse manager, employees, and farmers who buy seeds from the channel. Data analysis was conducted through a purely qualitative process of coding, grouping, and interpreting the data. The results show that the educational content presented by Gusman Bojonegoro is not only beneficial for experienced farmers but also a valuable guide for beginners. The videos produced provide a comprehensive overview of the challenges and solutions in shallot cultivation. Additionally, two-way interaction through video comments enables knowledge exchange that boosts productivity among the onion farming community. A comprehensive educational approach and the use of digital media as a marketing tool proved effective in increasing sales of Nganjuk variety shallot seeds, as well as expanding farmers' networks and knowledge in the digital era